Analysis Of Non-Tax State Revenue Calculation: Case Study At Nizam Zachman Ocean Fishing Port Referring To PP 85/2021 - Shantika, Shantika; John Pieris; Diana Ria Winanti Napitupulu (SEAN Institute, 2024)
This study has the main objective to explore and analyze the method of calculating non-tax state revenues for Mooring and Hygiene at the Nizam Zachman Ocean Fishing Port, with reference to Government Regulation Number 85 of 2021. In addition, this study also aims to explore and analyze non-tax state revenue optimization strategies, with a special focus on efforts to minimize potential losses at the Nizam Zachman Ocean Fishing Port. The research method applied is sociological empirical legal research with legal, case, historical, comparative, and conceptual approaches. The results showed two aspects of conclusions, first, related to the calculation of Non-Tax State Revenue (PNBP) for Mooring and Cleanliness at the Nizam Zachman Ocean Fishing Port, which has followed the formula based on Government Regulation No. 85 of 2021. The value of mooring services varies according to the Gross Tonnage (GT) of the ship, and the calculation of cleanliness involves the GT factor of the ship and the number of days. Second, optimization of fisheries business requires improvement in calculation formulation, emphasis on operational governance to reduce potential losses, and the search for new levy opportunities by considering Fisheries Management Areas (WPP) as a representation of fishing areas and fish resource potential, as well as the Non-Fisheries Product Collection Tax State Revenue (PNBP PHP) policy.